Young women smokers' perceptions and use of counterfeit cigarettes: Would plain packaging make a difference?. (June 2014) - Moodie, Crawford; Purves, Richard; Mckell, Jennifer; de Andrade, Marisa
<x xml:space="preserve">Abstract</x> Opponents of plain tobacco packaging argue that it would make production of counterfeit tobacco products cheaper; lower costs for consumers; confuse consumers in respect to product authenticity; and increase appeal and purchase of counterfeit tobacco. We explored the last of these contentions with young women smokers (N = 49), aged 16–24 years, recruited in Glasgow (Scotland). Participants were firstly asked about their perceptions and purchase of counterfeit cigarettes. Each group was then shown a mock display of legitimate and counterfeit plain cigarette packs. All the packs shown were the same colour (brown) with the only difference being the price and brand name. Participants were asked what brand they would smoke if all cigarettes came in brown (plain) packaging. Purchase of counterfeit cigarettes was lower for 16–17 year olds than 18–24 year olds. Perceptions of counterfeit cigarettes were negative, with concerns expressed about content and taste. All participants said that if pack appearance was standardised they would continue to smoke the same brand of legitimate cigarettes that they currently smoke or down-trade to cheaper legitimate brands. Non-users of counterfeit cigarettes indicated that they would remain non-users should all cigarettes come in uniform packaging. Counterfeit users, at least those willing to smoke counterfeit cigarettes again, indicated that they would still buy counterfeit cigarettes if pack appearance was standardised, primarily due to the lower price. For young women smokers in this study, plain packaging had no bearing on perceived appeal of counterfeit cigarettes.